Про антиплоску задачу лiнеаризованої магнiтострикцiї феритiв з феромагнiтним резонансом - Шульга, М.О. (Видавничий дім "Академперіодика" НАН України, 2007)
A new version of the theory of linearized magnetostriction for ferrites of a cubic system with ferromagnetic resonance for the antiplane problem of magnetoelasticity is offered.